Trace metals and metalloid elements in sediment cores (1940s-2017) and suspended particulate matter (2017-2018) from the Eure River, France - Thomas Gardes; Maxime Debret; Yoann Copard; Alexandra Coynel; Julien Deloffre; Matthieu Fournier; Sidonie Revillon; Jean Nizou; Anne-Lise Develle; Pierre Sabatier; Stéphane Marcotte; Edouard Patault; et al. (PANGAEA, 2020)
We measured trace metals and metalloid elements (TMMs) and isotopes of Pb in sediment cores (collected in two independant ponds) and Suspended Particulate Matter (SPM) (collected monthly) to estimate current and past flux, temporal trends, and source of TMMs since 1940s in the Eure River Watershed, major tributary of the Seine Estuary (France).